2005
DOI: 10.1080/00222930400014148
|View full text |Cite
|
Sign up to set email alerts
|

A new genus and six new species of the Parabathynellidae (Bathynellacea, Syncarida) from the Kimberley region, Western Australia

Abstract: Six new species of a new genus of the Parabathynellidae are described from the Kimberley Region, Western Australia. The erection of the new genus, Kimberleybathynella gen. nov., is based on the twosegmented antenna, the partial fusion of the second and third segments of the maxilla, and the setal condition of the uropodal exopodite, where the outer seta is longer than the inner one. The onesegmented exopodite of thoracopods I-VII and hemispherical form of male thoracopod VIII suggest the close relationship of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 15 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…Once again, previously unstudied aquifers have revealed new taxa of Bathynellidae, confirming the trend of diversification observed for many other stygofaunal groups in the Pilbara, including the Bathynellidae sister family Parabathynellidae (Cho et al, 2005;Hong & Cho, 2009;Cho & Humphreys, 2010;Abrams et al, 2012), the Tainisopidae and Phreatoicidae isopods (Knott & Halse, 1999;Wilson, 2003;Keable & Wilson, 2006;Finston et al, 2009), oligochaetes (Pinder, 2008;Brown et al, 2015) and the Paramelitidae amphipods (Finston et al, 2007(Finston et al, , 2008(Finston et al, , 2011.…”
Section: De Grey River Bathynellidae Diversitysupporting
confidence: 65%
“…Once again, previously unstudied aquifers have revealed new taxa of Bathynellidae, confirming the trend of diversification observed for many other stygofaunal groups in the Pilbara, including the Bathynellidae sister family Parabathynellidae (Cho et al, 2005;Hong & Cho, 2009;Cho & Humphreys, 2010;Abrams et al, 2012), the Tainisopidae and Phreatoicidae isopods (Knott & Halse, 1999;Wilson, 2003;Keable & Wilson, 2006;Finston et al, 2009), oligochaetes (Pinder, 2008;Brown et al, 2015) and the Paramelitidae amphipods (Finston et al, 2007(Finston et al, , 2008(Finston et al, , 2011.…”
Section: De Grey River Bathynellidae Diversitysupporting
confidence: 65%
“…Darwinulid ostracods were identified only to family level but subsequent work showed that four species occur in the Pilbara (Schon et al 2010). Syncarids were mostly identifi ed only to genus but genera have been shown to consist of multiple species in the Kimberley and Yilgarn (Cho et al 2005;Guzik et al 2008) and this is also the case in the Pilbara. The four species of Atopobathynella illustrated in Figure 9 were not distinguished during the survey, despite possessing some distinctive characters, because of the poorly developed state of syncarid taxonomy in Western Australia at the time when survey samples were processed.…”
Section: Taxonomic Limitationsmentioning
confidence: 99%
“…Wilson and Ponder 1992;Karanovic, I. and Marmonier 2002;Cho et al 2005;Susac et al 2010) but, while there has been relatively little survey in the Kimberley and publications are mostly taxonomic, it appears to have a less well-developed fauna than the Pilbara and Yilgarn (Hancock and Bennison 2005;Bennelongia 2012c). Poorly developed stygofauna communities also occur in south-western Australia and the Nullarbor region.…”
Section: Global Signifi Cance Of Pilbara Faunamentioning
confidence: 99%
“…Cho (2005), Cho et al (2005Cho et al ( , 2006aCho et al ( , 2006b), Cho and Humphreys (2010) Ostracoda Karanovic, I. Marmonier (2002, 2003), Karanovic (2003aKaranovic ( , 2003bKaranovic ( , 2004Karanovic ( , 2005aKaranovic ( , 2005bKaranovic ( , 2007) Copepoda Karanovic, T. Pesce and De Laurentiis (1996), Pesce et al (1996aPesce et al ( , 1996b, Karanovic et al (2001), Karanovic and Pesce (2002), Karanovic (2003Karanovic ( , 2004aKaranovic ( , 2004bKaranovic ( , 2005Karanovic ( , 2006 (1998) points (bores or caves).…”
Section: Methodology For Estimating Subterranean Faunal Diversitymentioning
confidence: 99%